Effect of Multiple Sclerosis and Its Treatments on Male Fertility: Cues for Future Research - Claudia Massarotti (MDPI AG, 2021)
Multiple sclerosis is a chronic disease that may lead to different types of symptoms and disabilities. with the better quality of life and decreased disability due to early diagnosis and the availability of disease-modifying therapies (DMTs), the treating physician is increasingly asked to counsel patients on its effects on fertility and reproduction. In particular, reproductive issues are still scarcely studied and discussed in men. Among the still open questions are the following: (a) Does multiple sclerosis cause infertility per sè? (b) Is multiple sclerosis correlated with conditions that increase the risk of infertility? (c) Do DMTs or other therapies for multiple sclerosis impact gonadal function in men? The aim of this review is to provide an overview on the available literature data about the reproductive issues unique to men with multiple sclerosis, underlining the numerous areas where evidence is lacking and, therefore, the priorities for future research.